Keswick and the East African Revival: An Historiographical Reappraisal - Bruner, Jason (Religion compass, 2011)
The history of the East African Revival has been understood predominantly from the perspective of British missionaries who were associated with the movement in the 1930s and 1940s. The most enduring of these narratives defined the revival by its relation to the English Keswick-influenced evangelicalism of the Western missionaries associated with the revival. This bias can be observed not only in the basic narrative of the revival, but also in the missionaries’ definition of ‘revival’, which served to exclude from considerations related groups that did not meet the missionaries’ standards. Subsequent historians and anthropologists have largely followed the lead of these initial missionary reporters of the revival. This has resulted in a historiography that conceives the movement primarily in its relationship to European missionaries in general and conservative British evangelicalism in particular. Consequently, significant dimensions of the revival’s impact upon late colonial East Africa have been neglected, such as the movement’s relationship to pre-Christian African religions, late colonial politics, African-language literature and literacy, and other contemporary movements of spiritual renewal. Investigation into such topics is only beginning to emerge with regard to the revival movement. What these varied studies indicate is that the history of the revival is best understood not in its relation to English evangelicalism, but rather as a Christian movement that was shaped by African hands, infused with African life, and carried with an African beat. It is, after all, an African story.